Live Not by Lies: A Man ual for Christian Dissidents. Rod Dreher - Василий Мацюк (Богословські роздуми: Східноєвропейський журнал богословʼя)
Live Not by Lies: A Man ual for Christian Dissidents. Rod Dreher. New York, U.S: Sentinel, 2020, 256 PP.; ISBN 9780593087398; 27.00 USD